Meningkatkan Kualitas Pelayanan Pastoral Melalui Penguatan Spritualitas Di GMIST Pusirungang Gangga Satu - Kota, Agnes; Adelin Bawues; Anatasia Pangku; Brilian Pondaag; Feiby Feronika Kawangung; Gloria Santa Klara; Kesya Taarae; Kristiani Makahingide; Pingky Pedati; Selna Bawental; Suzzet Parauba; Yusita Y Bulenoh (PT. Giat Konseling Nusantara, 2024)
The PKM program at GMIST Pusirungang Gangga Satu, led by 12 active students from the Institute of Christian Studies in Manado, aimed to address several issues within the community that required pastoral care. The program employed a qualitative descriptive research method, involving data collection through observation, interviews, and documentation. The students observed that the community faced several challenges that needed to be addressed through pastoral care. To address these issues, the students organized a seminar for the pastoral care providers at GMIST Pusirungang Gangga Satu, focusing on strengthening spiritualities to enhance the quality of service. The seminar aimed to improve the resolution of issues within the community through pastoral care.